Heterogeneity and Contribution of Microplastics From Industrial and Domestic Sources in a Wastewater Treatment Plant in Xiamen, China - Long, Zouxia; Wang, Wenling; Yu, Xingguang; Lin, Zhongyang; Chen, Jian (Frontiers in Environmental Science, 2021)
Plastic-related industrial discharge is suspected as a significant source of microplastics (MPs) in the influent of wastewater treatment plants (WWTPs). However, little is known about the characteristics of MPs in industrial wastewater. Taking the Haicang WWTP in Xiamen, China as an example, this study compared MPs in industrial wastewater with the domestic one in terms of abundance, particle size, polymer type, shape and color. Wentworth modulus, grain size parameters and principal component analysis (PCA) were performed to describe the MP difference between those two. It was found that the abundance of MPs in industrial wastewater was more than twice that in domestic wastewater, and the flux of MPs discharged into the aquatic environment through industrial wastewater was about 3.2 times that of domestic wastewater. The main shapes of MPs in industrial wastewater and domestic wastewater were fiber and granule, respectively. The proportion of polyester (PES) and polyethylene terephthalate (PET) in industrial wastewater was higher than that in domestic wastewater, related to the type of factories served by the WWTP. Compared with domestic wastewater, the rough surface of MPs in industrial wastewater was more complex and diverse, which might have a high capability of adsorbing other pollutants, thereby causing more significant harm to the environment. Our result supported that industrial sources of MPs are the priority areas in environmental management, and immediate action is taken to prevent industrial-sources MPs from entering the environment.